Performance Analysis Of Clustering Protocol Using Fuzzy Logic For Wireless Sensor Network - Vaibhav Godbole (IAES International Journal of Artificial Intelligence (IJ-AI), 2012)
In order to gather information more efficiently, wireless sensor networks are partitioned into clusters. The most of the proposed clustering algorithms do not consider the location of the base station. This situation causes hot spots problem in multi-hop wireless sensor networks. In this paper, we analyze a fuzzy clustering algorithm which aims to prolong the lifetime of wireless sensor networks. This algorithm adjusts the cluster-head radius considering the residual energy and the distance to the base station parameters of the sensor nodes. This helps decreasing the intra-cluster work of the sensor nodes which are closer to the base station or have lower battery level. In this paper fuzzy logic is utilized for handling the uncertainties in cluster-head radius estimation. We compare this algorithm with LEACH according to first node dies, half of the nodes alive and energy-efficiency metrics. Our simulation results show that the fuzzy clustering approach performs better than LEACH. Therefore, the fuzzy clustering algorithm is a stable and energyefficient clustering algorithm.DOI: http://dx.doi.org/10.11591/ij-ai.v1i3.1259